The Characterization of an 99, 5% Al2O3 Coating Deposited on a Ti Alloy and Subjected to Thermal Shock. (2015) - Pintilei, Geanina Laura; Abrudeanu, Marioara; Munteanu, Corneliu; Daniel, Dragomir-Stanciu; Crismaru, Ionut Vasile
Abstract: The behavior of the material subjected to thermal shock is influenced by its phase stability, its micro structural properties and its thermal expansion properties. This paper analysis the behavior of an 99, 5% purity Al2O3 deposited on a Ti alloy subjected to thermal shock with the purpose to determine the possibility to improve parts made from Ti alloy that work in high temperature transient conditions. The sample was subject to thermal shock at a maximum temperature of 1200 °C. The maximum temperature was reached in 12 seconds and the cooling of the part to room temperature was done also in 12 seconds. To determine the influence of the thermal shock on the materials SEM and XRD analysis were done before and after the thermal shock on the sample. Finite element analysis was done to determine the stress distribution in the due to thermal expansion of the materials.